Theoretical and empirical analysis of the supplier induced demand in health care market in China. Issue 2 (29th July 2014) - Li, Jun-Shan; He, Pei-Pei; He, Rui-Bo
Abstract : Purpose: – The purpose of this paper is to provide theoretical model about supplier-induced demand (SID) in health care market in China. Then, an empirical analysis will also be carried out according to the theoretical model above. At last, some advices will be provided in order to control or eliminate the SID in Chinese health care market. Design/methodology/approach: – SID has in fact been one of the most contentious topics in the economics of health care. According to the SID theory in health economics, the theoretical model about SID in China has been provided, then, based on the co-integration theory, the empirical analysis has been brought out. Findings: – The study tells that it is the reduction of government finance to hospital, not the increase of supply that is the long-term steady determinants of growth of health care expenditure and that the difference of marginal return to hospital among all kinds of services and medicines is the external factor. Originality/value: – To provide theoretical model about SID in health care market in China is the main originality value.